If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6x + 7) + -9 = 18x + 12 Reorder the terms: 3(7 + 6x) + -9 = 18x + 12 (7 * 3 + 6x * 3) + -9 = 18x + 12 (21 + 18x) + -9 = 18x + 12 Reorder the terms: 21 + -9 + 18x = 18x + 12 Combine like terms: 21 + -9 = 12 12 + 18x = 18x + 12 Reorder the terms: 12 + 18x = 12 + 18x Add '-12' to each side of the equation. 12 + -12 + 18x = 12 + -12 + 18x Combine like terms: 12 + -12 = 0 0 + 18x = 12 + -12 + 18x 18x = 12 + -12 + 18x Combine like terms: 12 + -12 = 0 18x = 0 + 18x 18x = 18x Add '-18x' to each side of the equation. 18x + -18x = 18x + -18x Combine like terms: 18x + -18x = 0 0 = 18x + -18x Combine like terms: 18x + -18x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3(1-5x)=x+19 | | 3r+2s-4t=-24 | | 11x-7x=36 | | 8x+4=x+20 | | 72d-45+13=12d-2 | | 91x^3+8x+9x^2= | | 2b+3+2(2b+3)+3(2b+3)=477 | | .1(x+11)=-2(8-x) | | -2y+2=-2(3y+17) | | 11-x/4=2-x | | 84=(2w+2)w | | 5B-52=93 | | m^2+4m+4= | | 10-x-3=5x-13-4x | | 6(5x+6)=1-5x | | x^2=2.89 | | 13.50+74=85.7 | | -8x=-2x+4x | | 15x+0.5=25x+0.25 | | 3y^4-(4y^4+3)= | | 7b-9=5b+13 | | 45p=180 | | 3c(4c+6)-18=168 | | 5(8+9d)=-21 | | 3(6x-12)=2x+44 | | 8x-5x=33 | | 11(y-3)=7(2-3h) | | 6k-3(k-8)=162 | | 4(x-10)=-3(2-x)-x | | 6=-4.9t^2 | | -3x-3y=-3 | | 3b^2=10b |